The School Health Program Development Model to Realize Healthy School Movement (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The School Health Program (UKS) aims to improve the health status of students through the Trias UKS, which includes health education, health services, and fostering a healthy school environment. However, the implementation of UKS has not been optimal in many schools, including Muhammadiyah 1 Elementary School in Malang, which faces challenges such as students' lack of knowledge about balanced nutrition, Clean and Healthy Living Behavior (PHBS), and mental health. This community service activity included planning, implementation, and evaluation phases. The program was conducted with 19 fourth-grade students at Muhammadiyah 1 Elementary School in Malang through lectures, demonstrations, and training methods. Interventions included education on balanced nutrition, PHBS, handling bullying, first aid training, and developing a healthy environment through TOGA (medicinal plants) cultivation. Evaluations were conducted to assess changes in students' knowledge, attitudes, and behavior. There was a significant increase in students' knowledge, with the percentage of students demonstrating good knowledge rising from 76% to 95% after the intervention. A total of 85% of students were able to independently practice handwashing and toothbrushing, and 60% could demonstrate first aid. High participation rates were observed in physical exercise and TOGA cultivation activities. The use of lecture methods supported by PowerPoint presentations and demonstrations contributed to positive changes in students' healthy living behaviors. The development program of UKS based on the Healthy School Movement (GSS) effectively improved students' knowledge, attitudes, and behaviors related to health. This model can be adopted to optimize UKS in schools through structured, interactive, and integrated health education methods to create a sustainable healthy school environment that supports the optimization of students' health and education quality.